Criteria for architect selection and satisfaction among first-time private sector clients - Oluwatayo, Adedapo Adewunmi (FormAkademisk, 2016)
For sustained profitability, architects must position themselves to attract new clients. This involves understanding potential clients’ choices and how these might impact on subsequent satisfaction. The study ranked criteria for architect selection and how these predict satisfaction among first-time private sector clients in Lagos, Nigeria. Data from a questionnaire survey were analysed using descriptive statistics, relative importance index and categorical regression, identifying timely delivery, cost of service and quality of previous services as the most important criteria. Although personal relationship has been said to influence selection of a professional service provider, this criterion was found to be of relatively low importance here. To attract private sector clients, architects should prioritise improved service delivery and construction skill development.